Effect of aminophylline on restoration of spontaneous respiration and recovery profiles during anesthesia without using muscle relaxants in patients undergoing brief gynecological procedure - Y.S. Jeon; E.H. Jun; J.H. Kim; S.T. Choi; J.H. In (Clinical and Experimental Obstetrics & Gynecology, 2020)
Purpose of Investigation: The purpose was to evaluate the effects of aminophylline on returning of spontaneous respiration and recovery profiles during propofol-fentanyl-sevoflurane anesthesia without muscle relaxants in patients undergoing day care gynecological surgery. Materials and Methods: Sixty-six patients were enrolled. Either aminophylline 3 mg/kg (group A) or saline (group C) was administered to each patient. Tidal volume (Vt), respiratory rate (RR), and end tidal carbon dioxide (ETCO2), apneic time, recovery time, discharge time and modified observer’s assessment of alertness/sedation scale (MOAA/S) were evaluated. Results: Apneic time and recovery time were significantly shorter in Group A than in Group C (P < 0.01). MOAA/S, tidal volume (P = 0.02) and ETCO2 (P = 0.03) were significantly improved in Group A compared with Group C. Conclusion: Aminophylline effectively reduced apneic and recovery time, thereby improving respiratory and recovery profiles during anesthesia with propofol, fentanyl, and sevoflurane in brief day care surgeries.